Complexity theory and the social sciences : the state of the art - Byrne, David; Callaghan, Gillian (Oxon : Routledge, 2023)
"This expanded and updated edition revisits the use of complexity theory across the social sciences and demonstrates how complexity informs approaches to various contemporary issues in the context of the COVID-19 pandemic, widening social inequality, and impending social and ecological catastrophe wrought by global warming."--
Keywords: Social sciences--Mathematical models; Chaotic behavior in systems; Social sciences--Research.